Economic Entomology in the 21st Century, as Seen from a Bibliometric Analysis of Its Leading Journal, 2000–2015. Part I: Topics and Commodities. Issue 4 (2nd October 2017) - Stankus, Tony
ABSTRACT: In their world leading publication, the Journal of Economic Entomology, economic entomologists typically found papers published between 2000-2015 roughly subdivided by type of crop attacked, venue of infestation, classic methodologies and more modern subspecialties, and recurring issues. The commodities most intensively studied include alfalfa, corn, cotton, garden vegetables, rice, soybeans, temperate climate tree fruits, tropical fruits, turfgrass, and wheat. Infested venues and procedures for their pest prevention, control or eradication were frequently explored and include both those used for the quarantining and treatment of newly imported commodities, as well as for the longer term post-harvest dry storage typical for cereal grains in warehouses. Household pests and structurally damaging termites remained topics of ongoing high interest.